Sources of language anxiety - Abdul Aziz, Noor Hashima; Abdul Samad, Arshad (2005)
Anxiety plays an important role in language learning because it ranks high among factors that can influence language learning (Oxford, 1999). It affects not only the way in which learners perform but also the way in which they perceive their performance (MacIntyre, 1999). In order to understand language anxiety, the sources of language anxiety need to be explored. This study was conducted to explore the sources of language anxiety from the students’ (UUM) perspectives. A qualitative case study was selected for this study. The sampling of participants (students) was done through purposive sampling in order to select information-rich cases. The main data collection was done mainly through interviewing language students. Interviewing lecturers and analyzing documents were done to triangulate the students’ perspective. his study found that the most cited sources of language anxiety were associated with speaking and writing skills. Another skill mentioned was related to listening comprehension. In this study, the sources of language anxiety stemmed from the learner, peers, instructional practice, personality, past experiences and language testing condition. Six themes emerged from the study. The themes were derived by associating language anxiety with three language skills, i.e. speaking, writing and listening, mentioned by the participants. The six themes which emerged from this study were belief and self-deprecating thought, afraid of being put on the limelight, afraid of being laughed at by peers, the type of lecturer or teacher, bad past experiences, and anxiety during language test.